Driving sustainable consumption: the role of green innovation, creativity and media in shaping consumers’ purchase intentions in Malaysia - Haris Fadzilah, Asmaul Husna; Ahmed, Areej; Ramdzan Ali, Al Amirul Eimer; Hassan, Mohammad Mujaheed; Ramli, Mohd Safwan (Springer Nature, 2025)
As environmental concerns continue to influence global consumer behavior, this study aims to investigate the impact of Green Innovation, Green Creativity, and Green Media on consumer Purchase Intention, with a focus on the Malaysian context. A structured survey was conducted among 312 consumers familiar with eco-friendly products, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the relationships between constructs. The findings reveal that Green Innovation and Green Media significantly influence Purchase Intention, whereas Green Creativity does not show a direct significant effect. These results suggest that consumers prioritize functional and communicative aspects of green marketing over creative design in shaping sustainable purchasing behavior. The study contributes to the theoretical development of green marketing by offering an integrated model and highlights the practical importance of aligning green marketing strategies with consumer expectations. Implications are provided for marketers and policymakers seeking to foster environmentally responsible consumption and enhance sustainability-driven engagement in emerging markets like Malaysia.